Expert System for Diagnosing Diseases Tubercolosis Using Bayes Method In Puskesmas Petumbukan - Muhammad Ridho Syahwana; R. Mahdalena Simanjorang (Journal of Computer Networks, Architecture and High Performance Computing, 2020)
Tuberculosis is an infection caused by acid-fast bacilli (AFB). Tuberculosis is an infectious disease apat affect anyone over the air. Tuberculosis is an infectious disease berbahaya.Tuberculosis a chronic or chronic disease that can strike between the age of 15-35 years. How to diagnose tuberculosis is by way of the expert of experts interviewed then test sputum samples using a lab to determine the positive or negative tuberculosis disease so it takes a long time. Therefore it takes an expert system with Bayesian methods to facilitate the penykit diagnosing tuberculosis. This expert system developed using Microsoft Visual Studio 2010 as well as by using Microsoft Access 2010 database.